Corporate community involvement : the definitive guide to maximizing your business' societal engagement - Lakin, Nick. (Stanford University Press ; Greenleaf, 2010)
The book's advice is backed by inspiring interviews with best-in-class practitioners from businesses like Microsoft, GlaxoSmithKline, Ericsson- as well as leading experts in corporate responsibility and community involvement. The text highlights best-practice approaches, effective methods, and concise tools to help managers "get there faster" and "get it right first time." The core of the book is a step-by-step guide that shows readers how to: conduct a current state analysis and devise a strategy; organize staffing and budgets; integrate corporate community involvement throughout the business and create high-profile programs' partner across sectors; measure and evaluate results; communicate successful activities; and overcome challenges.